Synanthropisation and synurbisation of raven "Corvus corax" in Poland: a review - Zawadzka, Dorota; Zawadzki, Grzegorz (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
The Raven "Corvus corax" is one of the oldest synanthropic bird species. Historical development of human settlements and cities was the reason of occupancy by ravens neighborhood of villages and town. Nowadays, suburban areas are, among forest and rural areas, habitats used by Ravens. Since end of middle ages Ravens began breeding in interior of towns in the Great Britain. During 20th century Raven occupied several big cities of Europe and North America.
Keywords: wróblowe; ornitologia